Bacterial Spectrum of Spontaneously Ruptured Otitis Media in a 7-Year, Longitudinal, Multicenter, Epidemiological Cross-Sectional Study in Germany - Imöhl, Matthias; Perniciaro, Stephanie; Busse, Andreas; van der Linden, Mark (Frontiers in Medicine, 2021)
We analyzed middle ear fluid (MEF) and nasopharyngeal swabs (NPS) from spontaneously ruptured AOM cases occurring in children under 5 years in Germany. Aims of the study were the assessment of disease burden and bacterial etiology in the era of routine pneumococcal vaccination. Furthermore, we aimed to compare isolates from MEF with isolates from NPS, and analyze the Streptococcus pneumoniae serotype distribution. We analyzed MEF and NPS samples in children two months to five years for vaccination status, frequency of bacterial strains, serotype/emm-type distribution of Streptococcus pneumoniae, Haemophilus influenzae and Streptococcus pyogenes as well as intra-individual correlation between MEF and NPS. From 2008 to 2014, MEF samples were collected from 2138 subjects of which 2001 (93.6%) also provided an NPS sample. In 851 of 2138 MEF samples (39.8%), we identified organisms with confirmed pathogenic potential; Streptococcus pyogenes: 315 (14.7%), Streptococcus pneumoniae: 170 (8.0%), Staphylococcus aureus: 168 (7.9%), Haemophilus influenzae: 133 (6.2%), Moraxella catarrhalis. Among NPS samples, 1018 (50.9%) contained Streptococcus pneumoniae, 775 (38.7%) Haemophilus influenzae, 648 (32.4%) Moraxella catarrhalis and 344 (17.2%) Streptococcus pyogenes. Over the seven study years, the number of AOM patients steadily decreased while the recruiting base remained constant. Streptococcus pneumoniae MEF isolates decreased by 86%, with serotype 3 being most prevalent (25.7%-42.9%). PCV13-non-PCV7-non-3 serotypes reduced to 0%. Among NPS, PCV7 serotypes decreased from 14.1% to 3.7%, PCV10: 17.6% to 3.7%, PCV13: 55.3% to 25.7%. PCV13-non-PCV7-non-3 serotypes increased in the first three years of the study (17.1% to 22.9%), then decreased to 4.6% in year7. Non-typeable Haemophilus influenzae reduced from 87.1% to 41.7% in MEF, and from 91.4% to 54.2% in NPS. MEF and NPS isolates from the same subject were identical for 91.9% of Streptococcus pneumoniae, 99.0% of Streptococcus pyogenes and 83.3% of Haemophilus influenzae. Among PCV7 vaccinated children, 5.6% had a PCV7 vaccine type in the MEF sample, among PCV13 vaccinated children 51.7% had a PCV13 serotype. Among non-vaccinated children, the percentages were 14.8 and 70.4. Pneumococcal conjugate vaccination has impacted the prevalence and etiology of spontaneously ruptured otitis media among children in Germany. Overall case numbers and pneumococcal vaccine type cases have strongly decreased.